Portföy performansının ölçülmesi A tipi yatırım fonlarının sharpe modeliyle değerlemesi - Özkaya, Kadir (My University, 2001)
In every period of time, investors try to be motivated to maximize their profit. The leading financial institutions, however, whose primary arm is to attract investors funds into financial markets act to maximize the return but minimize the risk. In developing countries, such as ours, investing into stocks is done via investor's own decisions whereas in well-developed countries this process is realised by professional institutions. In developing markets especially in Turkey, funds seem to be confidential. Investors prefer to make investments on their own in the boundless markets rather than using funds. This point is the primary reason why dounds and portfolio management remain idle and undeveloped. In this reserch, it is pointed out that measuring portfolio performance and publishing these data is essential to develop portfolio management. This rather practical reserch explains the differences between portfolio performances the foundemental scape of this research is to keep these confidential fundsfrom undiscovered position that investors always keep in their mind and is to prove that an easy of their measurement will be a guiding light to clarif their structure. To maintain this, in the first section of the research the concept of risk is presented. İn the following section, section two general framework of portfolio management is put forward whereas in the third section, the care of the research , portfolio performance measurement is told. The basis for this research was taken from data of A-type funds in Turkey beetween 1998-2000. Following this, on the fourth section general look to portfolio is developed. The fifth section mainly focuses on practical applications and their results. And finally the conclusion section ends the reserch. The primary aim of this research is to maintain a general concern about A-type funds which are the primary investors that develop stock exchange market and is to make conclusion on the management and measurement of these funds. In recent years, mant of speculations on investment funds arised. It is general concern that there is a need for additional precautions to finish these speculations. The market members have common idea that these funs are intesively inspected but their performances are not. Wherher funds are well-directed or not or what their success against alternatives is remains unknown some of the speculations on funds will be listed as fallows: - some of market players who are stuck in some stocks, are able to pass their stocks to general portfolio. - Portfolio managers and their relatives are alble to sell stocks to general portfolio on hidh prices. - Brokage firms raise the volume by making same-price-transactions. - Portfolio Management and investment consultancy fees reach to very high levels. It should be noted that to prevent these speculations, in addition to close inspections on fallowing the rules. There should also be inspections on portfolio performance. As it is pointed out in our research, it will be essential to publish these measurement on montly basis for both the investors and portfolio managers. Investors will prefer the portfolio directed by high performance groups and these groups will develop their portfolio by organising new ones. This process will result in deeper markets as new resources to economy are injected. In this competitive environment the other fund manegers will try to maximize their efficiency by setting higher goals. It is obvious that investment funds are inevitable needs for the cooperation in such a circumstance in which inflation and interest rate decrease. This is because consultancy and expertising become more important in these circumstances. In high interest rate periods, expertising is not much need for cooperations who invest their idle funds to repo. In the fallowing years, well-organised and not disclosed funds will be the sole medium that attract investors funs to capital market. In this research, we coclude that, there are big differences in portfolio performances. Our goal should be make performance measurement process common as it is in developed markets. This is the only way to create corporate identy and quality. Mainting corporate identity will be possible by increase in corporate investors and develeopment in investment fund will be possible by transparent processes such as annauncing portfolio performances. Corporate profile that would be created by understanding the structure of investment funds will act as a key to carry us to market desired.
Keywords: Ekonomi; Finansman ekonomisi; PORTFÖY ANALİZLERİ; Yatırım; Yatırım fonları